Advances and Perspectives for Polyploidy Breeding in Orchids - Bolaños Villegas, Pablo Alberto (2021)
The orchid market is a dynamic horticultural business in which novelty and beauty command high prices. The two main interests are the development of flowers, from the miniature to the large and showy, and their fragrance. Overall organ size might be modified by doubling the chromosome number, which can be accomplished by careful study of meiotic chromosome disjunction in hybrids or species. Meiosis is the process in which diploid (2n) pollen mother cells recombine their DNA sequences and then undergo two rounds of division to give rise to four haploid (n) cells. Thus, by interfering in chromosome segregation, one can induce the development of diploid recombinant cells, called unreduced gametes. These unreduced gametes may be used for breeding polyploid progenies with enhanced fertility and large flower size. This review provides an overview of developments in orchid polyploidy breeding placed in the large context of meiotic chromosome segregation in the model plants Arabidopsis thaliana and Brassica napus to facilitate molecular translational research and horticultural innovation.